Boosting the photocatalytic hydrogen production of TiO2 by using copper hexacyanocobaltate as co-catalyst. (8th March 2021) - Acevedo Peña, Próspero; Ramírez Ortega, David; Guerrero Araque, Diana; Hernández Gordillo, Agileo; Zanella, Rodolfo; Reguera, Edilso
Abstract: The development of cheap and efficient co-catalysts is crucial to improve the performance of well-known photocatalysts towards the hydrogen evolution reaction. Here, copper hexacyanocobaltate was evaluated for the first time as a potential candidate to be used as co-catalyst coupled with conventional TiO2 . Copper hexacyanocobaltate was formed by chemical precipitation in the presence of TiO2, without needing further treatments. The composite exhibited paramount performance towards hydrogen generation, surpassing by up to 16 times the behavior reached with bare TiO2 . This composite also overcome the performance of conventional TiO2 modified with copper and cobalt oxides derived from copper hexacyanocobaltate. The enhanced behavior of TiO2 /Cu3 [Co(CN)6 ]2 composite was promoted by the efficient separation of photogenerated charge carries, and the faster charge transfer from photocatalyst towards species in solution, as it was proved by the photoelectrochemical characterization of the materials. Furthermore, the composite experienced a slight detriment (15%) in its hydrogen production rate after four consecutive photocatalyst tests. This variation was attributed to the slow leaching of copper in the co-catalyst caused by its partial transformation into metal hydroxides, as it was suggested by the ex-situ XPS characterization. Nevertheless, the structural characterization evinced the presence of the Cu3 [Co(CN)6 ]2 in the composite after long-term use. This study should be considered a proof of concept on a reliable route to obtain appropriate composites for hydrogen production using light as primary energy source. Graphical abstract: Image 1 Highlights: Cu3 [Co(CN)6 ]2 was formed onto TiO2 by simple chemical precipitation. Characterization of composites evinced the formation of heterojunctions. Cu3 [Co(CN)6 ]2 improved the charge separation and charge transfer process in TiO2 . Hydrogen generation increase up to 16 times by using Cu3 [Co(CN)6 ]2 co-catalyst. Composites show good stability after four recycle tests of 7 h each.